2022
DOI: 10.1177/00938548221078296
|View full text |Cite
|
Sign up to set email alerts
|

Race and Ethnicity Differences in Police Contact and Perceptions of and Attitudes Toward the Police Among Youth

Abstract: While investigations examining the effects of direct and vicarious police stops on youth attitudes toward the police have been limited, even less research has explored how these processes vary by race/ethnicity. Thus, this study uses the Fragile Families and Child Wellbeing Study (FFCWS) to examine how race/ethnicity shapes: (1) the relationship between direct and vicarious police stops and youth attitudes toward police and (2) how the contextual nature of these stops (intrusiveness) influence youth perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…Researchers should pay special attention to conducting research with trans and gender-expansive youth at the intersection of other historically marginalized identities, especially across race, sexual orientation, SES, and geographic location (primarily given that local police departments vary significantly across urban and rural areas). Considering previous research has found Black and Latine youth are most likely to have negative perceptions of police (Foster et al, 2022;Hurst et al, 2022), race may intersect with gender and sexual orientation to play a unique role in determining trans and gender-expansive youths' perceptions of police.…”
Section: Implications For Police and Future Researchmentioning
confidence: 92%
See 2 more Smart Citations
“…Researchers should pay special attention to conducting research with trans and gender-expansive youth at the intersection of other historically marginalized identities, especially across race, sexual orientation, SES, and geographic location (primarily given that local police departments vary significantly across urban and rural areas). Considering previous research has found Black and Latine youth are most likely to have negative perceptions of police (Foster et al, 2022;Hurst et al, 2022), race may intersect with gender and sexual orientation to play a unique role in determining trans and gender-expansive youths' perceptions of police.…”
Section: Implications For Police and Future Researchmentioning
confidence: 92%
“…Researchers have postulated that youths’ perceptions of police are both informed through direct police encounters and through vicarious experiences with law enforcement (e.g., learning about police treatment through peers, family, etc. ; Foster et al, 2022; Harris & Jones, 2020; Hurst et al, 2022; Hurst & Frank, 2000). These direct and indirect experiences with police in childhood could potentially shape how youth perceive law enforcement into adulthood (A.…”
Section: Perceptions Of Policementioning
confidence: 99%
See 1 more Smart Citation
“…Themes that emerge from the qualitative research relate to how youths cope with vicarious and direct police contact and how that contact shapes the way they see and subsequently interact with the police (Brunson, 2007; Fox-Williams, 2019; Lee & Robinson, 2019; Nordberg et al, 2016, 2018; Payne et al, 2017; Weitzer & Brunson, 2009). Quantitative research has examined the impact of vicarious and direct police contact on youths’ future orientation (Testa et al, 2022), youths’ perceptions of procedural (in)justice (Foster et al, 2022; Harris & Jones, 2020; Slocum & Wiley, 2018), and youths’ legal cynicism and legal socialization (Geller & Fagan, 2019; Hofer et al, 2020). Given this growing body of qualitative and quantitative research, it is understandable that, from the youths’ standpoint, the police pulled their guns on them for no apparent reason.…”
Section: Prior Police Contact As a Construct Influencing Miranda Waiversmentioning
confidence: 99%
“…Police encounters are the most visible and commonly experienced form of criminal justice contact among youth (Friedman et al, 2004; Hurst & Frank, 2000), making policing highly relevant to youth’s legal attitudes (Geller & Fagan, 2019; Hofer et al, 2020; Jackson et al, 2020). Intrusive policing, as a procedurally unjust practice (Geller & Fagan, 2019), can have lasting implications for youth’s views toward authority figures and their compliance with the law (Foster et al, 2022; Hofer et al, 2020). For instance, aggressive and intrusive policing can cloud adolescents’ attitudes of law enforcement as unjust and illegitimate; in turn, youth who view the police as cynical have few reasons to abide by the law and thus are more likely to engage in more defiant behaviors (Fagan & Tyler, 2005; Miron & Brehm, 2006).…”
Section: The Spillover Effects Of Police Intrusion On Adolescents’ Sc...mentioning
confidence: 99%